Analysis of Drug-Induced Gastrointestinal Obstruction and Perforation Using the Japanese Adverse Drug Event Report Database - Satake, Riko; Matsumoto, Kiyoka; Tanaka, Mizuki; Mukai, Ririka; Shimada, Kazuyo; Yoshida, Yu; Inoue, Misaki; Hasegawa, Shiori; Iguchi, Kazuhiro; Ikesue, Hiroaki; Shimizu, Shinya; Nishida, Shohei; et al. (Frontiers in Pharmacology, 2021)
Drug-induced gastrointestinal obstruction (DIGO) and gastrointestinal perforation (DIGP) may be the result of gastrointestinal hypomotility and severe constipation, which may lead to potentially fatal complications of bowel ischemia, sepsis and perforation. We evaluated the onset profile of DIGs (DIGO and DIGP) associated with prescription drugs by analyzing data in the Japanese Adverse Drug Event Report (JADER) database. We selected 161 DIG-related drugs and categorized them into 19 classes based on the Anatomical Therapeutic Chemical (ATC) Classification System. Finally, we focused on 58 drugs and conducted subsequent analyses for the time-to-onset and outcomes. We extracted 79 preferred terms (PTs) with the strings “ileus,” “stenosis,” “obstruction,” “obstructive,” “impaction,” “perforation,” “perforated,” “hypomotility,” and “intussusception” from the Standardized Medical Dictionary for Regulatory Activities (MedDRA) Queries (SMQs) of SMQ20000104: gastrointestinal perforation, ulcer, haemorrhage, obstruction non-specific findings/procedures; SMQ20000105: gastrointestinal obstruction; and SMQ20000107: gastrointestinal perforation. Among the 667, 729 reports in the JADER database submitted between April 2004 and November 2020, we identified 11,351 occurrences of DIGs. The reporting odds ratios (RORs) (95% confidence interval) of “barium sulfate containing X-ray media,” “drugs for treatment of hyperkalemia and hyperphosphatemia,” and “oral bowel cleanser” were 142.0 (127.1–158.6), 25.8 (23.1–28.8), and 29.7 (24.8–35.6), respectively. The median number of days (interquartile range) until the onset of an adverse event caused by each drug category was as follows: barium sulfate containing X-ray contrast media (2.0 [1.0–3.0]), diazepines, oxazepines, thiazepines, and oxepines (8.0 [8.0–18.5]), drugs for treatment of hyperkalemia and hyperphosphatemia (29.0 [8.0–55.0]), non-selective monoamine reuptake inhibitors (19.0 [7.0–47.5]), and oral bowel cleanser (0.0 [0.0–0.0]). Depending on the drug, the time to onset of side effects ranged from days to several months. Our results highlighted the need to perform detailed monitoring of each drug for possible association with DIGs, which might otherwise have fatal consequences.